Striking down constitutional amendments: when do courts enhance democracy in Latin America? - Riccetto, Pedro Henrique Arcain (2020)
The role of the Courts in the review of constitutional amendments is often pictured as a detractor of the democratic quality of a political system, as many scholars argue it endangers the will of a qualified elected majority. However, there may be cases where the judicial intervention enhances democracy by improving the political decisionmaking standards. The dissertation aims to answer under which circumstances the power granted to justices to review constitutional amendments produces democratic outcomes. To address the question, I considered institutional and political settings of several Latin American countries (Argentina, Brazil, Colombia, and Peru) and performed a comparative analysis to test whether the presence or absence of some variables allows a democratic judicial review of constitutional amendments. The political and institutional attributes discussed are (I) Judicial Independence, (II) Political Competition, and (III) Legitimacy of the Courts, identified from previous literature in judicial politics. I tested if the presence of these variables fulfils three criteria established as a measure for democracy: (i) the existence of deliberative processes inside and outside the courts, (i) the possibility of overrides and backlashes, and (iii) the nonpartisanship of the judicial rulings, in the review of constitutional amendments. I then chose two countries for the testing of each attribute (I, II, III), one where this attribute is present and another where it is absent. For testing this model, I adopted the rational choice theory applied to judicial behaviour. The results show that the presence of some combinations of institutional attributes enhance the democratic quality of the judicial review of constitutional amendments. The dissertation intends to provide scholars with a better understanding of the constitutional amendment dynamics. It also aims to develop a tangible guide to assist constitutional practitioners on deciding the role of the courts in the judicial review of constitutional amendments and determining what are the best institutional scenarios for granting justices with this power.